Educational Wastage Quantitative bat vocational training institutions in Ouargla Province (El-Wahat Journal for Research and Studies, 2021)
Vocational training sector is one of the most important tools of the country for the preparation of human capital and the development of individual skills, especially that the latter is among the significant mechanisms of activating economic growth of each society. Despite its importance, vocational training encounters various obstacles that prevent achieving its aims on the individual and the community levels so that it would result in prosperity and progress of the society. One of these obstacles is the phenomenon of educational wastage. Thus, the present study tried to investigate educational wastage at vocational training institutions in Ouargla Province (south-east of Algeria) during the period (2014-2016). Results are displayed in tables for easy to read, followed by analyze qualitative analysis for these results. Keywords- educational wastage-Vocational training- Trainees.